REVIEW: KETERSEDIAAN OBAT INDIKATOR DAN DISPARITAS WILAYAH PADA UPTD FARMASI DINAS KESEHATAN DI INDONESIA - Dora Dewi Rahmahwati; Faizal Hermanto (Jurnal Buana Farma, 2026)
Drug availability is one of the main indicators of the quality of health services in Indonesia. Effective drug planning and distribution in the Regional Technical Implementation Unit (UPTD) of the Health Office Pharmacy is key to ensuring public access to essential drugs. This review aims to evaluate drug planning and distribution indicators in the UPTD Pharmacy of Health Offices throughout Indonesia based on recent published studies. A narrative review was conducted through a systematic search of academic databases for the period 2024-2025. Inclusion criteria included studies that evaluated drug planning, distribution, and availability in Indonesian health facilities. Data extracted included study location, study design, sample size, drug availability rate, planning accuracy, and stock-out rate. Of the 12 studies analyzed, drug availability rates varied between 78.5% and 95.2%, with an average of 87.5%. Medicine planning accuracy ranged from 75.2% to 98.5%. Stock-out rates showed significant variation between 4.1% and 22.1%, with an average of 13.7%. The study in Medan with the implementation of Distribution Requirement Planning showed the best results with 95.2% availability and 98.5% planning accuracy. Eastern Indonesia, such as Keerom and East Sumba, showed lower performance with availability below 85%. There are significant disparities in drug planning and distribution between regions in Indonesia. The implementation of integrated information systems and data-based planning methods such as Distribution Requirement Planning can improve drug availability and reduce stockouts. Special attention is needed in remote and eastern regions of Indonesia to improve access to essential drugs.